Low-Cost Implementation and Satisfaction in Kota Bharu, Kelantan - Wan Mohd Nawi, Wan Syamuri (2004)
The main objective of this study was to determine the role of State Government and private developers in implementing low cost housing program in Kelantan from 1980 to 2000. The specific objectives were to identify the socioeconomic background of the respondents; to identify the relationship between housing satisfaction and housing improvement; to determine significant factors that contribute to residential satisfaction, and to identify housing satisfaction of respondents towards their housing according to the type of the house. A total of three hundred low income households from two types of houses namely single storey terrace houses in Pengkalan Chepa and flats in Kampung Sireh in Kota Bharu areas were randomly selected and interviewed using questionnaires. Multivariate regression was used to determine significant variables that contributed to residential satisfaction. The results of the study showed that low cost housing units were built by the government and private sectors for the lower income group. The state of Kelantan was governed by Barisan Nasional from 1980 to 1990. When PAS Party took over Kelantan in 1990, the Federal government terminated the financial support to the state government which prevented them to build any low cost unit during the period. The result of the study showed that the household size was between 5 to 6 person. Most husbands and wives were between 47 to 51 years. Their average monthly income was RM990. In terms of housing, the result revealed that they were not satisfied with the size of the kitchen and the number of bedrooms. Those staying in terrace houses were more satisfied with their house compared to those in flats because the design of terrace house permitted them to improve the houses as their income increased. In terms of overall residential satisfaction, satisfaction towards services available received the highest level of satisfaction followed by housing unit and facilities. T-test indicated a significant difference in residential satisfaction which implied that those who stayed in terrace houses were more satisfied with their dwelling as compared to those who stayed in flats. The T-test also indicated there was a significant difference between respondents who added number of bedrooms and those who did not, with regards to residential satisfaction. Multivariate regression analysis indicated significant variables that contributed to the residential satisfaction were the total cost on housing improvement and the number of bedrooms. It showed that housing satisfaction increased as cost of housing improvement and number of bedroom were increased.The results of this study revealed that certain factors could cause households to be dissatisfied with their houses. Households in the terrace houses were more satisfied with their house because they could modified their house compared to those who stayed in flats. Thus, housing planners should take into consideration several aspects like household aspiration, affordability, ability and ways of life of the occupants in planning and implementation of housing for this group. Alternative housing designs should help to reduce space deficit especially among those households who have no choice but to stay in their present house. Ignoring this factor could result in residential dissatisfaction and social problems. The relationship between planning and meeting the needs of the target group indicated that housing dissatisfaction is a result of the failure of public and private sectors in delivering affordable and quality housing for the occupant. The consequence of difference political ideologies adopted by the federal and state governments were felt by the people, especially those who are in the low income group. As a result they were denied of basic facilities to meet their basic needs.